Trends and Patterns in Age Discrimination in Employment Act (ADEA) Charges. (July 2016) - von Schrader, Sarah; Nazarov, Zafar E.
The Age Discrimination in Employment Act (ADEA) protects individuals aged 40 years and over from discrimination throughout the employment process. Using data on ADEA charges from the Equal Employment Opportunity Commission from 1993 to 2010, we present labor force–adjusted charge rates demonstrating that the highest charge rates are among those in the preretirement age range, and only the rate of charges among those aged 65 years and older has not decreased. We examine characteristics of ADEA charges including the prevalence of different alleged discriminatory actions (or issues) and highlight the increasing proportion of age discrimination charges that are jointly filed with other antidiscrimination statutes. Through a regression analysis, we find that the likelihood of citing various issues differs by charging party characteristics, such as age, gender, and minority status, and on charges that cite only age discrimination as compared to those that are jointly filed. Implications of these findings for employers are discussed.